A Non-Nested Test of Separability for Flexible Functional Forms - Moschini, Giancarlo (The Review of Economics and Statistics, 1992)
This paper develops a separable functional form in which all the relevant aggregator functions are modeled.to the desired degree of approximation. This leads to separable structures that are more flexible than those implied by parametric restrictions of flexible functional forms. Tests of separability can then be accomplished in a nonnested framework. This approach is illustrated with an application to input-output separability for a multiproduct translog cost function using a robust likelihood ratio testing procedure. Copyright 1992 by MIT Press.